Comparison of table tennis serve and return characteristics in the London and the Rio Olympics - Wang, J. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to evaluate the changes in table tennis serves and return of serves between the London (2012) and Rio (2016) Olympic Games. The sample consisted of 30 matches corresponding to 60 player-games with 3,009 serves and 2,961 returns from rounds four to finals. Notational analyses were conducted to examine the stroke positions, ball placements, and stroke efficacies for serves and returns as well as stroke types for returns. Wilcoxon or Mann-Whitney U tests were used to quantify the differences of different categories of each variable within the same Games or between the two Games. From the 2012 Games to the 2016 Games, significant increases were found in the middle short placement of serve (p < 0.01) and flip return (p < 0.01). Significant decreases were found in half placements of serve (p < 0.05), very good serve (p < 0.05), backhand return (p < 0.05), very good return (p < 0.01), very poor return (p < 0.05), and topspin returns (p < 0.01). These findings indicated a more balanced serve and return from the 2012 Games to the 2016 Games, which may inform coaches and players for taking corresponding countermeasures.